2003
DOI: 10.1109/led.2003.815944
|View full text |Cite
|
Sign up to set email alerts
|

Study of nickel silicide contact on Si/Si1-xGex

Abstract: The properties of nickel silicide formed by depositing nickel on Si P + Si 1 x Ge x layer are compared with that of nickel germanosilicide on P + Si 1 x Ge x layer formed by depositing Ni directly on P + Si 1 x Ge x layer without silicon consuming layer. After thermal annealing, nickel silicide on Si P + Si 1 x Ge x layer shows lower sheet resistance and specific contact resistivity than that of nickel germanosilicide on P + Si 1 x Ge x layer. In addition, small junction leakage current is also observed for ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Recently, SiGe technology was introduced into high-performance strain-induced CMOS technology. [1,2] A high quality of nickel germanosilicide is nec-essary as well. In this paper, the abnormal oxidation and agglomeration on Si and SiGe substrates are discovered after high-temperature post-silicide annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SiGe technology was introduced into high-performance strain-induced CMOS technology. [1,2] A high quality of nickel germanosilicide is nec-essary as well. In this paper, the abnormal oxidation and agglomeration on Si and SiGe substrates are discovered after high-temperature post-silicide annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Although metal germanosilicide contact with low resistivity can be formed on borondoped SiGe film, such contact is prone to morphological degradation and higher resistivity at elevated annealing temperature due to germanium segregation [1]. It has been found that by using a Silicon capping layer on SiGe, the nickel silicide (NiSi) contact formed showed improved morphological stability and electrical characteristics compared with the nickel germanosilicide contact formed directly on SiGe [2]. With this regard, epitaxial growth of boron-doped silicon (Si:B) has recently drawn increasing attention.…”
mentioning
confidence: 99%